2004
DOI: 10.1016/s0002-9440(10)63226-9
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblasts Express the Inflammatory Cytokine Interleukin-6 in a Murine Model of Staphylococcus aureus Osteomyelitis and Infected Human Bone Tissue

Abstract: Staphylococcus aureus is the single most common cause of osteomyelitis in humans. Incidences of osteomyelitis caused by S. aureus have increased dramatically in recent years, in part due to the appearance of community-acquired antibiotic resistant strains. Therefore, understanding the pathogenesis of this organism has become imperative. Recently, we have described the surprising ability of bone-forming osteoblasts to secrete a number of important immune mediators when exposed to S. aureus in vitro. In the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 27 publications
6
50
1
Order By: Relevance
“…Marriott et al (22) demonstrated that osteoblasts express IL-6 during bacterial bone infection in a mouse model and in human bone tissues. IL-6 (12, 17) and IL-1␤ (4,25), which are produced by stimulated monocytes/macrophages, stimulate osteoclasts and lead to bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…Marriott et al (22) demonstrated that osteoblasts express IL-6 during bacterial bone infection in a mouse model and in human bone tissues. IL-6 (12, 17) and IL-1␤ (4,25), which are produced by stimulated monocytes/macrophages, stimulate osteoclasts and lead to bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…Although the immunosuppressive function of DOC is promising, it cannot be ignored that DOC gradually expressed MHC class II and lost their suppressive activity in vivo. It is reported that POC expressed all immune surface markers which can elicit an immune response, and they are able to act as APCs (42)(43)(44)(45)(46). Hence, it is predicted that DOC in vivo are going the way their progeny normally does.…”
Section: Discussionmentioning
confidence: 99%
“…4 To date, much of our knowledge of the pathogenesis of OM comes from animal models, 5 which have existed in chicken, 6 rat, 7,8 guinea pig, 9 rabbit, 10 dog, 11 sheep, 12 goat, 13 and most recently mouse. 14 While these models have been used to confirm the importance of bacterial adhesions identified from in vitro assays, [15][16][17] none of them contain quantitative endpoints that can determine bacterial load or growth in vivo. Thus, they are of limited value for assessing drug effects, bacterial mutants, and the role of host factors during the establishment of chronic OM.…”
Section: Introductionmentioning
confidence: 99%